2011
DOI: 10.1080/10887156.2011.570137
|View full text |Cite
|
Sign up to set email alerts
|

Differences in managerial jobs at the bottom, middle, and top: A review of empirical research.

Abstract: It has become popular in the practices of leadership development and talent management to segment managers at different organizational levels in order to focus on the unique requirements thought to characterize jobs at each level. This movement has been spurred by popular books that emphasize differences in the nature of managerial work at different hierarchical levels. Seemingly independent of popular work in this area has been scientific research to describe differences in managerial jobs across organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…One study found that successful senior managers spend more time learning about the organisational culture than those who are not successful but also warned that it is the most difficult aspect to understand (Martin 2015). This has been echoed by other research that emphasised the importance of understanding what the new role entails within the systemic context and organisational culture (Kaiser et al 2011). …”
Section: Facing Challengesmentioning
confidence: 95%
See 1 more Smart Citation
“…One study found that successful senior managers spend more time learning about the organisational culture than those who are not successful but also warned that it is the most difficult aspect to understand (Martin 2015). This has been echoed by other research that emphasised the importance of understanding what the new role entails within the systemic context and organisational culture (Kaiser et al 2011). …”
Section: Facing Challengesmentioning
confidence: 95%
“…Moving into a senior leadership position is one of the key challenges that leaders need to face during their careers (Dotlich et al 2004). The concept of a leadership pipeline suggests that changes are required in individuals in terms of their appearance, knowledge, behaviour, attitudes and values as they progress up the ladder (Kaiser et al 2011). They face a so-called triple challenge of having to decide which aspects of their previous roles they need to let go of, which to preserve and which to build on (Freedman 2011 complexity where each level of work is related to the time span required by the executor to complete the task (Jaques 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is also a growing literature on the relationship between dark side variables and work success and failure (Furnham, Hyde, & Trickey, 2013, 2014a, 2014bGaddis & Foster, 2015;Judge, Piccolo, & Kosalka, 2009;Kaiser, Hogan, & Craig, 2008;Kaiser, Craig, Overfield, & Yarborough, 2011;. Hogan (2006) distinguishes three further aspects of personality, referred to as "the bright side", "the dark side", and "the inside".…”
Section: Introductionmentioning
confidence: 99%
“…This unique transition of employees is often characterized by changes in self-concept and perspectives, moving away from identifying with their peers to primarily identifying with the organization and managing former peers; and also new challenges beyond extant level of experience . Instead of doing the work themselves, first line managers begin to assume responsibility for supervision and the performance of others who carry out the day-to-day work of an organization (Kaiser, Craig, technical skills, the work demands more supporting incumbent in terms of interpersonal and conceptual skills -albeit less than what is demanded at more senior levels (Kaiser, Craig, Overfield, & Yarborough, 2011;McCauley, Moxley, & Van Velsor, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Overfield, & Yarborough, 2011). While these supervisory employees still require goodKanyangale & Pearse / International Journal of Organizational Leadership 3(2014) …”
mentioning
confidence: 99%